Pengembangan Media Pembelajaran Berbasis Powerpoint Padu Musik Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas 5 SDN 105326 Bangun Rejo - Muhammad Aldi, Beta Rapita Silalahi (Pusdikra Publishing, 2021)
The aim of the researcher is to describe the Development of PowerPoint-Based Learning Media with Music to Improve Social Studies Learning Outcomes for 5th Graders at SDN 105326 Bangun Rejo. This research is a type of research with a development model or Research and Development (R&D) with a research product, namely PowerPoint-based learning media. Based on the results of inferential statistical analysis using the t test formula, it can be seen that the value is 43,640. With a frequency (dk) of 31 – 1 = 30 at a significance level of 5%, it is obtained = 1,571. Therefore > at a significance level of 0.05, the null hypothesis is rejected and the alternative hypothesis is accepted, and on the T-test, the Sig value is 0.000, which means that there is an influence in using Powerpoint-Based Learning Media with Music on the student learning outcomes in social studies subjects, especially on the subject of regional culture in Indonesia class V SDN 105326 Bangun Rejo. The results of the analysis above which show the influence of Powerpoint-Based Learning Media Unified Music are in line with the results of observations made, besides Cronbach's Alpha is obtained 0.820 which is Cronbach's Alpha > 0.7, then the data of Media-Based Learning Powerpoint Padu Musik is considered reliable or valid.